The Effectiveness of Project Based Learning on Students’ Social Attitude and Learning Outcomes - Rina Febriana (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This study aims at determining the effectiveness of the learning model of Project-Based Learning (PjBL) on students’ social behavior and learning outcomes. This study can be categorized as the quasi experimental method with pretest-posttest control group design. Data collection technique to measure students' social behavior was using questionnaires and to measure student learning outcomes was using post-test. Data analysis for student learning result was using U Mann Whitney test while the analysis on the social behavior of students was using descriptive analysis. The results of this study indicated that: (1) the student who stated that the learning model PjBL can increase the social behavior of students was 40.3%, the student who agreed was 39%, and the student who were hesitant with this learning model was 20.7% (2) the result of student learning outcomes with PjBL model increased with the mean score of 7.67 while the class with the conventional method was 4.67. The implications of the application of this model were the improvement of students’cognitive, affective, and psychomotor aspects.